Pengaruh Komunikasi Dan Disiplin Kerja Terhadap Stres Kerja Karyawan Pt. Primatech Engineering Medan - Shelly Shelly; Syawaluddin Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (STIE Amkop Makassar, 2023)
This research was conducted on employees who work at PT. Primatech Medan Engineering. The purpose of this study was to determine and analyze the effect of communication and work discipline on employee work stress. The population and sample in this study were found to be 50 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously communication and work discipline have a positive and significant effect on work stress of employees of PT. Primatech Medan Engineering. Partially, communication affects the work stress of PT. Primatech Medan Engineering. Partially, work discipline has a positive and significant effect on work stress of PT. Primatech Medan Engineering. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value is 0.316 which means that it explains that employee stress is 31.6% while the remaining 68.4% is influenced by variables that are not examined such as: work rotation, conflict, salary, and so on.